Wheat-Related Gastrointestinal Diseases: Narrative Review - Khan, Umael; Arslan Lied, Gülen (Turkish Journal of Gastroenterology, 2025)
Intolerance to wheat and gluten intake has gained public and scientific interest in recent years. Celiac disease (CD) and wheat allergy are wheat-related disorders with a well-defined etiological mechanism alongside corresponding diagnostic tests. In addition, patients also self-report intolerance toward wheat and gluten that does not meet the criteria of CD and wheat allergy. This gives rise to a third category, namely non-celiac wheat sensitivity (also referred to as non-celiac gluten sensitivity). However, this category is controversial. Unlike CD and wheat allergy, the pathophysiological mechanism is unknown. When conducting double-blinded placebo-controlled trials, only a small proportion of patients can correctly identify gluten from a placebo based on symptoms, indicating a substantial nocebo component. In fact, it has been posited that non-celiac wheat sensitivity is simply a form of irritable bowel syndrome. The aim of this review is to provide an overview of the epidemiology, etiology, clinical manifestations, diagnosis, and management of the 3 abovementioned conditions. Cite this article as: Khan U, Lied GA. Wheat-related gastrointestinal diseases: Narrative review. Turk J Gastroenterol. 2025;36(9):540-546.